miR-182 promoter hypermethylation predicts the better outcome of AML patients treated with AZA + VEN in a real-world setting - Yilan Xu; Danyang Li; Na Wang; Bei Ge; Chen Meng; Min Zhao; Zihan Lin; Min Li; Yigang Yuan; Yue Cai; Liuzhi Shi; Shenmeng Gao; et al. (Clinical Epigenetics)
Abstract Background 5-Azacytidine (AZA) combined with the BCL2 inhibitor Venetoclax (VEN) is the standard treatment for elderly acute myeloid leukemia (AML) patients or those who are unfit for intensive chemotherapy (elderly or unfit AML). However, an effective and rapid predictive biomarker to predict treatment outcome remains elusive. Methods miR-182 promoter methylation was measured in 94 AZA + VEN-treated elderly or unfit AML patients and 20 normal controls (NCs) samples. To determine whether miR-182 promoter methylation is a predictive marker of clinical outcomes in AZA + VEN-treated AML patients in a real-world setting, we analyzed and compared the complete remission (CR)/CR with incomplete hematologic recovery (CRi) rate, overall survival (OS), and leukemia free-survival (LFS) across different methylation groups: miR-182 promoter hypomethylation (median value < 20.21%) and hypermethylation (> 20.21%) in a retrospective study. Results The average methylation frequency was markedly higher in 94 AZA + VEN-treated elderly or unfit AML patients than that in 20 NCs. However, some AML patients (11.7%) still presented low miR-182 promoter methylation (< 10%). The average time to obtain CR/CRi was shorter in AML patients with miR-182 promoter hypermethylation than AML with hypomethylation. Moreover, the median OS and LFS were longer in AML patients with miR-182 promoter hypermethylation than AML with hypomethylation. Finally, the area under the curve (AUC) for 1-year mortality was 0.831, for 2-year was 0.788, and for 3-year was 0.800. Conclusions AML patients with miR-182 promoter hypermethylation have better outcomes. miR-182 promoter methylation is a predictive biomarker for AZA + VEN-treated AML patients.